Informing the future through foresight and metrics to accelerate food, land, and water system transformation - Gotor, Elisabetta; Wiebe, Keith D.; Thurlow, James; Enahoro, Dolapo K. (2022)
Awareness is growing in the research and development community of the interconnections between food, land, and water systems. We also recognize that jointly managing systems transformation under climate change and uncertainty can achieve more sustainable, equitable, and resilient development. Yet transformation means moving from our current state to a fundamentally different state in the future. What is that desired future state, and what actions are needed to get there? This event will outline how innovative use of data, state-of-the-art foresight analytics, and deep and ongoing dialogue with national, regional, and global partners – with particular focus on poor and vulnerable populations in low- and middle-income countries – can offer better insights into alternative future transformation pathways to inform choices and sharpen decision-making today.